2009
DOI: 10.1016/j.healun.2009.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Post-ischemic Infusion of Atrial Natriuretic Peptide Attenuates Warm Ischemia–Reperfusion Injury in Rat Lung

Abstract: Our results indicate that ANP administered at the onset of reperfusion increases cGMP in lung tissue and attenuates warm ischemia-reperfusion injury in isolated perfused rat lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…All the lungs were reperfused successfully in 80 min. Thus, consistent with previous reports [12–17], our isolated rat lung perfusion model remained stable throughout the observation period.…”
Section: Resultssupporting
confidence: 91%
“…All the lungs were reperfused successfully in 80 min. Thus, consistent with previous reports [12–17], our isolated rat lung perfusion model remained stable throughout the observation period.…”
Section: Resultssupporting
confidence: 91%
“…Studies have shown that ANP can not only protect the myocardium from damage caused by IRI (Kousholt, 2012) but can also have a protective effect on the lungs and liver. The mechanism of the protective effect of ANP is related to reduction in oxidative stress, inhibition of inflammation and inflammatory cell infiltration, and protection of endothelial function (Dodd-o et al, 2008;Aoyama et al, 2009;Yamada et al, 2013). A recent study on renal IRI reported that ANP also plays a protective role in ischemic renal injury (Koga et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[19] revealed that administration of ANP infusion at the onset of lung reperfusion attenuates reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%